ANALISIS EFEKTIVITAS METODE PEMBELAJARAN AKTIF DALAM PEMBENTUKAN KARAKTER DAN MORAL SISWA SEKOLAH DASAR - Fanny Tio Anderesta Siahaan; Flora Estetika Putri br Ketaren; Nicholas Gregorius Ginting; Wahyu Gusnanda Siburian (Sindoro: Cendikia Pendidikan, 2025)
This study uses a qualitative method with a descriptive approach to analyze the effectiveness of active learning methods in the formation of students' character and morals in SD No. 105293 Medan Estate. Data was collected through three main techniques, namely interviews, journal studies, and book studies. In-depth interviews were conducted with teachers, students, and parents to gain a direct understanding of their experiences and perceptions of the application of active learning methods in character education. In addition, this study also uses literature studies by examining various scientific journals and relevant books to enrich theories and support data analysis. The results of the interviews were then compared with findings in journals and books to get a more comprehensive picture of the effectiveness of the methods applied, the challenges faced, and strategies that can be developed to improve character education in primary schools.